2016
DOI: 10.1074/jbc.m115.707174
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic Maturation in Response to Shear Flow Is Mediated by the Activator Protein 1 (AP-1) Transcription Factor via Mitogen-activated Protein Kinase (MAPK) Mechanotransduction

Abstract: Megakaryocytes (MKs) are exposed to shear flow as they migrate from the bone marrow hematopoietic compartment into circulation to release pro/preplatelets into circulating blood. Shear forces promote DNA synthesis, polyploidization, and maturation in MKs, and platelet biogenesis. To investigate mechanisms underlying these MK responses to shear, we carried out transcriptional analysis on immature and mature stem cell-derived MKs exposed to physiological shear. In immature (day (d)9) MKs, shear exposure up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 77 publications
1
24
0
2
Order By: Relevance
“…In addition, NF-κB activation in the airways of allergen-challenged mice is attenuated by Toll-like receptor (TLR) 2 or TLR4 gene deletion, suggesting that TLR2 or TLR4 contribute to NF-κB signaling (16,17). Similarly, the AP-1 and STAT3 promoter-binding activity are regulated by MAPK and JAK/STAT signaling (18,19). Therefore, it was hypothesized that LPS may induce NF-κB, MAPK and JAK/STAT pathway activation, leading to NF-κB, AP-1 and STAT3 nuclear translocation and cytokine expression in the H292 and THP-1 cells investigated in the present study.…”
Section: Effect Of Lps Treatment On Nf-κb Ap-1 Ppar and Stat3mentioning
confidence: 99%
“…In addition, NF-κB activation in the airways of allergen-challenged mice is attenuated by Toll-like receptor (TLR) 2 or TLR4 gene deletion, suggesting that TLR2 or TLR4 contribute to NF-κB signaling (16,17). Similarly, the AP-1 and STAT3 promoter-binding activity are regulated by MAPK and JAK/STAT signaling (18,19). Therefore, it was hypothesized that LPS may induce NF-κB, MAPK and JAK/STAT pathway activation, leading to NF-κB, AP-1 and STAT3 nuclear translocation and cytokine expression in the H292 and THP-1 cells investigated in the present study.…”
Section: Effect Of Lps Treatment On Nf-κb Ap-1 Ppar and Stat3mentioning
confidence: 99%
“…Fibrinogen mediated adhesion and signaling is an important component of megakaryocyte differentiation, development, and proplatelet formation . Fibrinogen signaling also activates translation control pathways, including the PI3K and MAPK pathways . As noted above, in other cells PDK1 regulates two pathways that converge on translation: first, Akt, which activates mTORC1 mediated translation and second, ERK1/2, which activates MAPK mediated translation .…”
Section: Resultsmentioning
confidence: 97%
“…56 We have also demonstrated that JNK signaling is involved in shear-induced Mk maturation and platelet production. 57 mTOR is a major regulator of Mk development and maturation. 58 Here, we showed that CD41 expression was significantly lower at days 7 and 12 in cells treated with an mTOR inhibitor prior to co-culture with MkMPs ( Figure 5A & 5B).…”
Section: -5p Inducesmentioning
confidence: 99%